THE CORRELATION BETWEEN PARENTING AND GADGET SCREEN TIME ON SOCIAL INTERACTION OF SCHOOL-AGE CHILDREN - Ningrum, Dhiajeng Widya; Kusbiantoro, Dadang; Harmiardillah , Sylvi; Firmansyah, Rahmat Agung; Aristanto, Fajar Suci (Universitas Airlangga, 2025)
Introduction: The prevalence of social interaction disorders among school-age children remains high. Parental influence and excessive device usage are two key factors that affect children's social interactions. This study aims to examine the relationship between parenting styles, the duration of gadget use, and social interactions in school-age children. Methods: A cross-sectional design with a correlational analytical approach was employed in this study. The population consisted of 75 children, and a simple random sampling technique was used, resulting in a sample of 63 children. Data were collected using the Parental Authority Questionnaire (PAQ), a closed-ended survey instrument. The data were tabulated and analyzed using the Chi-square test. Results: The results revealed that most parents (38.1%) adopted a democratic parenting style, the majority of children (54.0%) spent more than two hours using technology, and the majority of children (52.4%) exhibited adaptive social interactions. The statistical analysis yielded a p-value of 0.000, indicating a significant correlation (p < 0.05) between school-age children's social interactions and the duration of gadget use. Conclusions: Based on these findings, it is recommended that parents closely monitor their children's technology use and establish time limits to prevent potential negative impacts on their social interactions with others.